2000
DOI: 10.1159/000013615
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin Antibodies in South African Patients with Lupus Nephritis: A Clinical and Renal Pathological Study

Abstract: Aims: This study was conducted prospectively to ascertain the prevalence of anticardiolipin antibodies (ACAs) in patients with lupus nephritis and to determine whether this subgroup of patients differed clinically and histologically from patients without the antibody. Patients and Methods: 40 SLE patients (26 Blacks, 14 Indians, 37 females, 3 males) with evidence of renal involvement underwent clinical assessment and percutaneous renal biopsy. Special investigations included: urinary protein quantitation; radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…aPL, including LAC, aCL, and anti-β2GPI antibodies, are considered to be of pathogenic significance in thrombosis in APS and SLE patients, which makes them the most frequently examined factors in the investigation of the pathogenesis of GMT in LN. GMT has been found to be associated with LAC and/or aCL in LN patients in some studies [ 4 , 6 , 7 , 9 - 12 , 14 - 18 ], but not in others [ 5 , 8 , 19 - 21 ]. Kant and colleagues [ 4 ] examined 105 kidney biopsy specimens from LN patients and found that GMT was detected in 34 cases, among which 7 were LAC positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aPL, including LAC, aCL, and anti-β2GPI antibodies, are considered to be of pathogenic significance in thrombosis in APS and SLE patients, which makes them the most frequently examined factors in the investigation of the pathogenesis of GMT in LN. GMT has been found to be associated with LAC and/or aCL in LN patients in some studies [ 4 , 6 , 7 , 9 - 12 , 14 - 18 ], but not in others [ 5 , 8 , 19 - 21 ]. Kant and colleagues [ 4 ] examined 105 kidney biopsy specimens from LN patients and found that GMT was detected in 34 cases, among which 7 were LAC positive.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory criteria of update criteria for definite antiphospholipid syndrome (APS) includes the lupus anticoagulant (LAC), the anticardiolipin antibody (aCL), and the anti-β2 glycoprotein I (β2GPI) antibody [ 13 ]. GMT has been associated with aPL in LN patients in some studies [ 4 , 6 , 7 , 9 - 12 , 14 - 18 ], but not in others [ 5 , 8 , 19 - 21 ]. Recent studies of seven monoclonal immunoglobulin (Ig) G aCLs from two APS patients demonstrated that five aCLs reacted with several hemostatic and fibrinolytic proteases that share homologous enzymatic domains.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of aPLs has been closely related to the development of thrombosis and pregnancy complications in antiphospholipid syndrome (APS). GMT has also been associated with aPLs in patients with LN in some studies, but the mechanism of aPL‐induced GMT is still a topic of controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have reported poor renal prognosis in patients with SLE and coexisting APSN. However, Naiker et al reported a high prevalence of aPL in patients with SLE nephritis but did not found worse renal prognosis ( 60 ).…”
Section: Introductionmentioning
confidence: 99%